Local Knowledge of the Sugihwaras Village Community of the Larung Offerings Tradition on Mount Kelud, Kediri Regency - Kartiko Sari, Laela Dwi; Kartika Indah, Novita (LenteraBio : Berkala Ilmiah Biologi, 2025)
Larung Offerings Kelud tradition is a traditional ceremony that requires plants. The relationship between plants and humans is studied in ethnobotany which has the potential to reveal local knowledge about biological resource diversity, conservation and culture. Therefore, this study aims to analyze the local knowledge of the community and the importance of plants used in the tradition of Larung Offerings Kelud. This study used a descriptive method with observation and interviews of five key informants as well as questionnaires to 30 participants. Participants were grouped by age, namely young (17-30), adult (31-44), middle-aged (45-60) and old (> 60 years). Community perception data were analyzed using a Guttman scale while the importance value used the fidelity level formula. The results showed that the perceptions people of aged 17-30 and 31-44 were good and low on the meaning of offerings and plants. Age 45-60 and >60 years old are very good and classified as good on the meaning of offerings and the meaning of offering plants. The highest importance of plants were rose (96.6%), cantil, jasmine and ylang (93.3%), coconut (90%), plantain (86.6%) and pandan wangi 83.3%; these plants were special plants that must be present in the tradition of Larung Offerings Kelud. The introduction of traditions along with plant species and their meanings needs to be carried out especially for the younger generation so that traditional knowledge is not lost. Research on local knowledge should be well documented because it is important information and plant diversity and culture in Indonesia remain sustainable.